THE USE OF NORMOTHERMIC EXTRACORPOREAL PERFUSION IN SITU IN KIDNEY ASYSTOLIC DONORS - Y.. A. Shcherbuk; S. F. Bagnenko; A. E. Scvorzov; I. V. Loginov; A. N. Ananyev; I. V. Ulyankina; S. V. Eremich; K. Y. Senchik; O. N. Reznik (Вестник трансплантологии и искусственных органов, 2010)
Deficit of donor organs is the limiting factor in organ transplantation. One way of solving this problem is the use of donors with sudden irreversible circulatory arrest. Obtaining organs from this category of donors is pos- sible only through the use of normothermic extracorporal perfusion in situ (NECP) with oxygenation and leu- cocyte depletion. The article presents the implementation of NECP in 11 uncontrolled non heart beating donor (uNHBD) kidneys (age of 43,1 ± 2,98 years) and the results of transplantation in 22 recipients of such transplants in comparison with the results of the 20 recipients of kidney transplants from 20 donors to the death of the brain (age 45,65 ± 1,8 years). Despite the initially high rate of delayed function and more significant number of hemo- dialysis in uNHBD group (group of investigation), serum creatinine at 21st day was the same level as in BDD group (comparison group): 0,198 ± 0,002 mmol/L and 0,151 ± 0,002 mmol/L (p > 0,05). The use of NECP with oxygenation and leucocyte depletion is an effective practice for recovery kidney from donors with a sudden ir- reversible circulatory arrest with warm ischemic time one hour and more before the operation explantation.